Method of checking the function of implanted artificial valve by pulsed Doppler echocardiography – in vitro study - GROŠPIC, Antonín; KOUDELKOVÁ, Eva; NIEDERLE, Petr; KLIMEŠ, František (Archives of Acoustics, 1984)
The usefulness of pulsed Doppler echocardiography for verifying the function of implanted Bjork-Shiley tilting disc valve prosthesis was checked experimentally in vitro. The valve was built into a physical model of central blood circulation. This arrangement permitted simulating examination of the implanted valve by a pulsed Doppler device with the advantage of simplified and well defined hydrodynamic conditions.Detection of valvular insufficiency is very sensitive and specific in contrast to valvular obstruction. This is due to the masking of the hydrodynamic signs of obstruction by flow disturbances downstream the valve despite its normal function.The same experience was made following the clinical application of pulsed Doppler echocardiography in our Institute. The examination technique has become a routine part of the periodic postoperative follow-up of patients with implanted artificial valves.